Perancangan Dan Implementasi Sistem PPDB Berbasis Web Pada Yayasan Islam Citra Matahari Menggunakan Metode Rapid Application Development (RAD) - Wulandari, Iin; Ariel Sanjaya, Kennanda; Bagus Pangestu, Raka; Ilham, Farizi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The student admission process (PPDB) at Yayasan Islam Citra Matahari is still carried out manually, leading to inefficiencies in administration, limited access to information, and unstructured data management. This study aims to design and implement a web-based information system for PPDB to facilitate the registration process and manage student data more effectively. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative development through prototyping and direct user feedback. The implementation results show that the system improves registration efficiency, broadens access to school information, and supports centralized, secure, and structured data management.